Effect Cookies Made from (Musa acuminata Cavendish and Cucumis sativus) and Self Talk against Reducing Urine Protein Levels and Blood Pressure in Women of Childbearing Age Pre Hypertension - Aswita; Kartini Kartini; Titi Purnama Delano (Journal of Liaquat University of Medical & Health Sciences, 2024)
OBJECTIVE: This study aimed to determine the influence of cookies made from (Musa acuminata cavendish and Cucumis sativus) and self-talk to reduce urine protein levels and blood pressure in women of childbearing age before hypertension. METHODOLOGY: The study was quasi-experimental, using pretests and post-tests from September to November 2023. Random sampling was done using the Slovin formula. Samples were divided into four groups; each group consisted of 30 people. The total sample consisted of 120 people. Data collection instruments included questionnaires, booklets, and cookies. Data were analyzed using SPSS Software with an independent t-test and ANOVA. RESULTS: There were differences in urine protein levels between the initial and final measurements. In group one, five respondents had positive urine protein, while 24 had negative urine protein. In group two, four patients had positive urine protein levels, and all of them were negative. In group three, 2 had positive proteins, and 28 had negative proteins. In group four, 2 had positive proteins, and 28 had negative proteins. A p-value of 0.000 indicates the influence of Musa acuminata Cavendish and Cucumis sativus cookies and the self-talk module on protein levels. CONCLUSION: Musa acuminata Cavendish and Cucumis sativus cookies and the Self Talk booklet for prehypertensive mothers in Kendari City for 12 weeks can effectively reduce blood pressure and urine protein levels.